2014
DOI: 10.1186/1749-7922-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of maxillofacial trauma in emergency department

Abstract: IntroductionThe incidence and epidemiological causes of maxillofacial (MF) trauma varies widely. The objective of this study is to point out maxillofacial trauma patients’ epidemiological properties and trauma patterns with simultaneous injuries in different areas of the body that may help emergency physicians to deliver more accurate diagnosis and decisions.MethodsIn this study we analyze etiology and pattern of MF trauma and coexisting injuries if any, in patients whose maxillofacial CT scans was obtained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
75
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 21 publications
10
75
2
2
Order By: Relevance
“…The age group affected was 18-39 years which was also concordant with our study (18-30 years had 20% cases and 31-40 years had 34.67% cases totalling 54.67% of the reported cases) but the main cause in their study for ZMC fractures was interpersonal assault as opposed to our results which was RTA. 18 Balakrishnan from India also reported age group 20 to 40 being more prone to RTAs which was also concordant with our results. 19 Nerve injury following fracture may present with various pathophysiology involving traction, pressure, ischemia, inflammation and physical damage of the infra-orbital nerve resulting in sensory neuropathy and motor functions in the area of innervation of infra-orbital nerve both as presenting symptom and as a postoperative complication.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The age group affected was 18-39 years which was also concordant with our study (18-30 years had 20% cases and 31-40 years had 34.67% cases totalling 54.67% of the reported cases) but the main cause in their study for ZMC fractures was interpersonal assault as opposed to our results which was RTA. 18 Balakrishnan from India also reported age group 20 to 40 being more prone to RTAs which was also concordant with our results. 19 Nerve injury following fracture may present with various pathophysiology involving traction, pressure, ischemia, inflammation and physical damage of the infra-orbital nerve resulting in sensory neuropathy and motor functions in the area of innervation of infra-orbital nerve both as presenting symptom and as a postoperative complication.…”
Section: Discussionsupporting
confidence: 82%
“…17 Arslan et al from Turkey reported 2.8:1 male to female ratio. 18 However our result showed a male: female ratio of 5:3, the difference in the ratios can be due to high RTAs in females as they commonly accompany males especially on the motorbike which is itself a major cause of RTA. The age group affected was 18-39 years which was also concordant with our study (18-30 years had 20% cases and 31-40 years had 34.67% cases totalling 54.67% of the reported cases) but the main cause in their study for ZMC fractures was interpersonal assault as opposed to our results which was RTA.…”
Section: Discussionmentioning
confidence: 63%
“…These fractures occur commonest in young adults especially males in third and fourth decades of life because they are majorly involved in many outdoor activities and reckless driving [5,9,10,12]. This assertion is supported by our study in which more than 75% of the study populations were males and 68.6% were between the ages of 20 to 40 years.…”
Section: Discussionsupporting
confidence: 77%
“…This is as a result of the centrality of the facial region as a key factor in human identity, esthetics, and general well-being [1,2]. These injuries can affect both skeletal and soft tissue structures of the facial region [3,4] and often times, based on the etiology and mechanism of injury, occur in association with other systemic injuries thereby requiring multidisciplinary approach for their management [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…They found that etiologic factors, demographic properties, and fracture patterns yielded various results due to social, cultural, and governmental differences, and MF trauma was more prevalent in young males as a result of interpersonal violence (15).…”
Section: Discussionmentioning
confidence: 99%